2011
DOI: 10.1111/j.1748-3743.2010.00263.x
|View full text |Cite
|
Sign up to set email alerts
|

Prescribing for older people in nursing homes: strategies to improve prescribing and medicines use in nursing homes

Abstract: Interventions to improve prescribing in the nursing home environment are many and varied. The critical literature review presented in Paper 1 (Parsons et al., 2011, International Journal of Older People Nursing 6, 45-54) in this series discussed the main issues repeatedly identified as problematic, and this paper summarises the main approaches which have been used to attempt to improve prescribing. These include national legislation which demands documented justification for the prescribing of medicines, medic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 48 publications
0
11
0
2
Order By: Relevance
“…Despite concerns surrounding inappropriate polypharmacy, there is increasing interest in appropriate polypharmacy, particularly in older people with multiple co‐morbidities. Appropriate polypharmacy has been identified as an approach to improve the quality of drug therapy in the nursing home setting (Gurwitz, 2004), and will be discussed in the next paper in this series (Parsons et al , 2011).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite concerns surrounding inappropriate polypharmacy, there is increasing interest in appropriate polypharmacy, particularly in older people with multiple co‐morbidities. Appropriate polypharmacy has been identified as an approach to improve the quality of drug therapy in the nursing home setting (Gurwitz, 2004), and will be discussed in the next paper in this series (Parsons et al , 2011).…”
Section: Resultsmentioning
confidence: 99%
“…In this article, the first in a series of three articles examining pharmaceutical issues in nursing homes, we seek to consider the key issues surrounding prescribing and use of medicines in the nursing home setting. Ways of influencing medication use in nursing homes will be discussed in detail in the second paper in this series (Parsons et al , 2011), while paper 3 (Hughes et al , 2011) will speculate as to what could be the key considerations in respect of medicines for nursing homes in the future.…”
Section: Introductionmentioning
confidence: 99%
“…The strategies outlined in Paper 2 (Parsons et al , 2011a) are approaches that have been shown to improve prescribing and medication use, but apart from the policy approach taken with Omnibus Budgetary Reconciliation Act (OBRA) there have been few national or comprehensive strategies to oversee prescribing in nursing homes. Indeed, the literature also suggests that even with a national policy such as OBRA, there is marked variation in prescribing patterns across nursing homes.…”
Section: Influences On the Quality Of Prescribing In Nursing Homesmentioning
confidence: 99%
“…The two previous papers in this series (Parsons et al , 2011a,b) have highlighted important issues about medications in nursing homes and proposed strategies to improve the processes and outcomes associated with prescribing medications. Of course, we are working under the assumption that nursing homes as we currently understand them will continue to be providers of long‐term for older people.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation